A study on design and experimental setup for microchannel condensers - Doan, Minh Hùng; Nguyen, Trọng Hiếu; Dang Thành Trung (Journal of Technical Education Science, 2015)
The developing an experimental setup for microchannel condensers was done in this study. In addition, the paper also showed experimental results on two microchannel condensers with water as the working fluid for the cases of vertical and horizontal microchannels. These experimental results obtained from this system are reliable, so this system can be used for experiments of microchannel heat transfer, etc.